Hubungan Asupan Karbohidrat Terhadap Kadar Trigliserida Pada Penderita Diabetes Melitus Tipe II Rawat Jalan Di RSUD Sukoharjo - Darmawan Biyantara, Hanif, Elida Soviana, S.Gz., M.Gizi (2016)
Background: Diabetes melitus uncontrolled will lead to complications of various diseases like stroke, hypertension, and heart disease. The complications due to the uncontrolled intake of carbohydrates and the level of triglycerides. The level of triglycerides influenced by intake of carbohihydrates and the productions of triglycerides. Extra calories especially comes from carbohydrate which will increase the production of the levels of triglycerides in the liver. Purpopse of the research: This research aimed to understand the relationship between intake of carbohydrates toward the level of triglycerides in patients type 2 Diabetes melitus. Methods of the research This research was an observasional with the cross-sectional approach. The data of intake carbohydrates were obtained from 4x24 hour food recall. Laboratory checks to the levels of triglycerides used TMG 24I premium. Analysis of the data used Spearman Rank correlation test. Result: The intake of carbohydrates were low. The subject who had high levels of triglycerides was 56,5 % and 43,5 % of the subject have levels of triglycerides normal. According to the Rank Spearman test the relationship between intake of carbohydrates and the levels of triglycerides in patients with diabetes melitus II showed pvalue = 0,044. The Conslusion: There was relationship between the intake of carbohydrates and the levels of triglycerides of diabetes melitus type II outpatients in hospitals Sukoharjo. The sugestion: Hospitals Sukoharjo are expected to increase human resources in optimally especially in providing education to the patient about the management of diabetes melitus to control the levels of triglycerides. Futhermore patients of diabetes melitus are expected to reduce the intake of foods that contain carbohydrate in order to reduce triglycerides and prevent complications. Key words: intake of carbohydrate, triglycerides, diabetes melitus Bibliography: 23 ( 1989 - 2009)